ATEX Unit verification process development for Ex motors - Kaminen, Juho (My University, 2017)
There are several Ex standards and local legislations around the world which define safety requirements for motors used in potentially explosive atmospheres. The legislation in EEA countries is the ATEX Directive, which requires Ex motors to be certified according to a conformity assessment procedure. One of these procedures is called the ATEX unit verification process, which leads to a machine-specific certificate issued by a third party notified body. The objective of the thesis is to clarify the requirements of the ATEX unit verification process and to study the current state and key challenges of the process in the case organization ABB Motors and Generators production unit Induction Machines, located in Helsinki. Additionally, the objective is to study how the case organization can improve recognizing the need to execute the unit verification process and how to improve the process to be more self-steering. The requirements of the ATEX Directive and the harmonised standards are studied in the literature review of the thesis. In the empirical study, a current state analysis is performed in order to find solutions for the research questions introduced. As a result of the current state analysis, the current process chart, analyzed statistical data and the key challenges in the ATEX unit verification process are introduced. Based on the results of current state analysis, a two-phased solution including a short-term and a long-term development proposal for the current unit verification process are introduced. The short-term proposal includes an improved process chart with a new certification work queue combined with documentation management. Also, a checklist for recognizing the need for executing the unit verification process and a process for instrumentation certificate management are introduced. The long-term proposal introduces an ideal large-scale process which can be implemented after the short-term proposal. It requires structural changes which are not easily adapted in the organization. The introduced proposals give answers to the research questions by solving the key challenges introduced in the current state analysis of the thesis.
Keywords: ATEX; unit verification; Ex certification; explosive atmospheres; process development; fi=Sähkötekniikka|en=Electrical Engineering|; fi=Sähkö- ja energiatekniikan koulutusohjelma (DI)|